2020
DOI: 10.1016/j.jeurceramsoc.2020.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Structural and photoelectrochemical properties of SrTaO2N oxynitride thin films deposited by reactive magnetron sputtering

Abstract: Sputtering deposition of SrTaO2N films on different types of substrates  Films approach stoichiometry with a bandgap of 2.33 eV when substrate temperature increases to TS = 800°C  Different degrees of film crystallization, from weakly crystallized to fully c-axis oriented, were obtained  Three limiting factors are identified: 1) low absorption coefficient; 2) short lifetimes of excited charge carriers; and 3) permittivity with moderate values  Dual effects of a higher crystallinity and a greater absorbance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…Nevertheless, it is commensurate with the values reported for a 150 nm SrTaO2N film photoanode grown on Ta sheet by reactive RF magnetron sputtering. 30 In this report, the enhanced photocurrent was clearly observed upon expanding the film thickness by adjusting the sputtering duration. 30 This photocurrent density is also higher than a 162 nm LaTiO2N and a 177 nm CaNbO2N thin film photoanodes prepared by a modified PLD method on a TiN layer with (001)-oriented supporting MgO, in which photocurrent density less than 1 µA cm −2 was recorded at 1.23 VRHE.…”
Section: Photoelectrochemical Water Oxidationmentioning
confidence: 59%
See 2 more Smart Citations
“…Nevertheless, it is commensurate with the values reported for a 150 nm SrTaO2N film photoanode grown on Ta sheet by reactive RF magnetron sputtering. 30 In this report, the enhanced photocurrent was clearly observed upon expanding the film thickness by adjusting the sputtering duration. 30 This photocurrent density is also higher than a 162 nm LaTiO2N and a 177 nm CaNbO2N thin film photoanodes prepared by a modified PLD method on a TiN layer with (001)-oriented supporting MgO, in which photocurrent density less than 1 µA cm −2 was recorded at 1.23 VRHE.…”
Section: Photoelectrochemical Water Oxidationmentioning
confidence: 59%
“…30 In this report, the enhanced photocurrent was clearly observed upon expanding the film thickness by adjusting the sputtering duration. 30 This photocurrent density is also higher than a 162 nm LaTiO2N and a 177 nm CaNbO2N thin film photoanodes prepared by a modified PLD method on a TiN layer with (001)-oriented supporting MgO, in which photocurrent density less than 1 µA cm −2 was recorded at 1.23 VRHE. 59 In this regard, the present result is promising and the performance is likely to be further improved through extending the oxynitride film thickness and to apply to porous 3D substrates.…”
Section: Photoelectrochemical Water Oxidationmentioning
confidence: 59%
See 1 more Smart Citation
“…[22][23][24] This renders semi-transparent quaternary metal oxynitrides generally as very promising photoanode candidates for PEC tandem cells, which could outperform Ta 3 N 5 -based devices. So far, semi-transparent quaternary metal oxynitride films have been mainly fabricated by means of reactive radiofrequency (RF) magnetron sputtering [25][26][27][28] or pulsed laser deposition (PLD) 29,30 on MgO or Nb:SrTiO 3 substrate. In case of the RF approach, the oxynitride sputtering targets have to be made first with multi-step processes, and harsh conditions (usually up to 1073 K for film deposition) are required, too.…”
mentioning
confidence: 99%
“…In case of the RF approach, the oxynitride sputtering targets have to be made first with multi-step processes, and harsh conditions (usually up to 1073 K for film deposition) are required, too. 27 The development of photoelectrode materials with more narrow band gaps than Ta 3 N 5 and hematite is mainly motivated by the higher theoretical light absorption capacity. 11 Recently, Domen et al have demonstrated a core-shell heterojunction photoanode of Ta 3 N 5 -nanorods/BaTaO 2 N, generating a stable photocurrent owing to efficient generation and extraction of charge carriers.…”
mentioning
confidence: 99%